Early Detection of Aβ Deposition in the 5xFAD Mouse by Amyloid PET. (28th February 2018) - Oh, Se Jong; Lee, Hae-June; Kang, Kyung Jun; Han, Sang Jin; Lee, Yong Jin; Lee, Kyo Chul; Lim, Sang Moo; Chi, Dae Yoon; Kim, Kyeong Min; Park, Ji-Ae; Choi, Jae Yong
Abstract : Purpose. 18 F-FC119S is a positron emission tomography (PET) tracer for imaging β -amyloid (A β ) plaques in Alzheimer's disease (AD). The aim of this study is to evaluate the efficacy of 18 F-FC119S in quantitating A β deposition in a mouse model of early amyloid deposition (5xFAD) by PET. Method . Dynamic 18 F-FC119S PET images were obtained in 5xFAD (n = 5 ) and wild-type (WT) mice (n = 7 ). The brain PET images were spatially normalized to the M. Mirrione T2-weighted mouse brain MR template, and the volumes of interest were then automatically drawn on the cortex, hippocampus, thalamus, and cerebellum. The specific binding of 18 F-FC119S to A β was quantified as the distribution volume ratio using Logan graphical analysis with the cerebellum as a reference tissue. The A β levels in the brain were also confirmed by immunohistochemical analysis. Result . For the 5xFAD group, radioactivity levels in the cortex, the hippocampus, and the thalamus were higher than those for the WT group. In these regions, specific binding was approximately 1.2-fold higher in 5xFAD mice than in WT. Immunohistochemistry supported these findings; the 5xFAD showed severe A β deposition in the cortex and hippocampus in contrast to the WT group. Conclusion . These results demonstrated that 18 F-FC119S PET can successfully distinguish A β depositions in 5xFAD mice from WT.